Incursion of Goths into the Roman province of Dalmatia and their impact on social-political, economic and cultural processes - Imamović, Mersiha (Historical Thought, 2025)
This study deals with the phenomenon of the Goths in the Roman Empire, their conflicts and alliances with the Western and Eastern part of the Empire and their relationship to the existing population and its material goods. In a very complex and difficult political and military situation, the Goths were found in the Roman province of Dalmatia. Some parts of this province at the beginning of the fifth century were influenced by the Visigoths, then from the half of the fifth century under the governance of the Pannonian Ostrogoths, and finally, at the end of the fifth century, the entire province of Dalmatia was ruled by Ostrogoths. Unlike the Visigoths which cannot be attributed nothing to merit in terms of positive changes in the areas that they occupied, Ostrogoths still left a very strong mark in the history of the Roman province of Dalmatia, especially in Bosnian and Herzegovinian and Croatian territories, where they ruled until 537th year.